2023
DOI: 10.1080/0886022x.2022.2120821
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with DHA and BMSCs suppressed podocyte injury and attenuated renal fibrosis by modulating the TGF- β 1/Smad pathway in MN mice

Abstract: Artemisinin has immunomodulatory, anti-inflammatory, and antifibrotic effects. Some studies have demonstrated that artemisinins have a protective effect on the kidney. DHA is a derivative of artemisinin and has effects similar to those of artemisinin. Human bone marrow-derived mesenchymal stem cells (BMSCs) accelerate renal repair following acute injury. In the study, we investigated the effects of combination therapy with DHA and BMSCs on membranous nephropathy (MN) mice. The 24-h urinary protein, serum total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Therefore, the observed decrease in the expression of podocin in renal tissues of rats treated with glycine in this study suggests a preservation of the structural integrity of renal tissues and therefore indicates that glycine is a potent renoprotective agent against renal toxicities associated with CoCl 2 exposures. Recent experimental studies also confirmed high expression of podocin as a novel biomarker of renal damage during acute kidney injury [49][50][51]. In conclusion, the results of this study clearly demonstrate the protective effects of glycine against tissue injuries and derangement of normal physiological functioning of the hepatic and renal systems in rats.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Therefore, the observed decrease in the expression of podocin in renal tissues of rats treated with glycine in this study suggests a preservation of the structural integrity of renal tissues and therefore indicates that glycine is a potent renoprotective agent against renal toxicities associated with CoCl 2 exposures. Recent experimental studies also confirmed high expression of podocin as a novel biomarker of renal damage during acute kidney injury [49][50][51]. In conclusion, the results of this study clearly demonstrate the protective effects of glycine against tissue injuries and derangement of normal physiological functioning of the hepatic and renal systems in rats.…”
supporting
confidence: 72%
“…Therefore, the observed decrease in the expression of podocin in renal tissues of rats treated with glycine in this study suggests a preservation of the structural integrity of renal tissues and therefore indicates that glycine is a potent renoprotective agent against renal toxicities associated with CoCl 2 exposures. Recent experimental studies also confirmed high expression of podocin as a novel biomarker of renal damage during acute kidney injury 49–51 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation